Immunohistochemical expression and significance of MMP1 in oral squamous cell carcinoma in relation to tumour depth - Murad, Ali Hassan; Al-Faroon, Mahdi Sukker (Journal of Stomatology, 2017)
Introduction. Oral squamous cell carcinoma (OSCC) is a malignancy of stratified squamous epithelium, beginning as an epithelial dysplasia and progressing until the dysplastic epithelial cells break the basement membranes (BM) and invade the underlying connective tissue. It is estimated that over 90% of all oral neoplasms are OSCCs. Matrix metalloproteinase-1 (MMP1) is an enzyme that in humans is encoded by the MMP1 gene which causes degradation of the extracellular matrix (ECM) and BM, and thus may play a key role in development and local invasion of OSCC. It can serve as a potential biomarker molecule for diagnosis, treatment and prognostic evaluation. Tumour depth (TD) is considered to be a more reliable feature, as many studies have shown that the risk of metastasis and spread to cervical lymph node (LN) increases with an increase in TD. Materials and Methods. Forty-five formalin-fixed, paraffin-embedded blocks of totally excised OSCC collected pro- and retrospectively were included in this study. Hematoxylin & Eosin stain was performed for each block for reassessment of histopathological examination. An immunohistochemical (IHC) staining was performed using anti-MMP1 monoclonal antibodies. Results. The majority of the OSCC sample revealed TD of more than 7 mm (57.78%), with a maximum registered depth of 18 mm. Furthermore, the data demonstrated a significant correlation between TD and cervical lymph node metastasis. Immunohistochemically, the tumour cells mostly showed MMP1 overexpression in score 4 (55.56%). Statistically, the MMP1 showed significant correlation with TD. Conclusion. A significant correlation was seen regarding the expression of MMP1with TD suggesting that degradation and collagenolytic activity against collagens in carcinoma tissue extract was associated with deeper invasion.